2010
DOI: 10.1007/s10549-010-1081-y
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms of the ataxia telangiectasia mutated gene and breast cancer risk: evidence from the current studies

Abstract: Epidemiological studies have evaluated the association between ataxia telangiectasia mutated (ATM) gene polymorphisms and breast cancer risk. However, published data are still inconclusive. We performed a meta-analysis for the first time, based on currently available evidence, by searching PubMed, ISI Web of Knowledge, and Embase databases to derive a more precise assessment of the relationship. Following the inclusion and exclusion criteria, nine publications were included in this meta-analysis. Of these stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
1
7
0
Order By: Relevance
“…Up to now, 5 meta-analyses have been performed for the role of the rs1801516 polymorphism on cancer risk: 4 on breast cancer [8, 4648] and 1 on thyroid cancer [49]. One of the meta-analyses showed that homozygous carriers of the rs1801516 genotype had a lower breast cancer risk compared with carriers of the heterozygous and homozygous wild-type genotypes [48]. However, the other studies did not find a significant association between the rs1801516 polymorphism and cancer risk [8, 46, 47, 49].…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, 5 meta-analyses have been performed for the role of the rs1801516 polymorphism on cancer risk: 4 on breast cancer [8, 4648] and 1 on thyroid cancer [49]. One of the meta-analyses showed that homozygous carriers of the rs1801516 genotype had a lower breast cancer risk compared with carriers of the heterozygous and homozygous wild-type genotypes [48]. However, the other studies did not find a significant association between the rs1801516 polymorphism and cancer risk [8, 46, 47, 49].…”
Section: Discussionmentioning
confidence: 99%
“…
We read with great interest the recent article by Lu et al [1] which assessed the association between polymorphisms of the ataxia telangiectasia mutated (ATM) gene and breast cancer risk with a meta-analysis involving five studies of 2,604 cases and 1,973 controls. This was an important investigation as the association has been inconsistent based on the previous individual studies.
…”
mentioning
confidence: 99%
“…GG: OR = 0.78, 95% CI 0.59-1.04). After carefully reading the two articles, we noted several methodological issues in the study by Lu et al [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Large-sample case-control studies have assessed effects of this polymorphism on risk of breast cancer, prostate cancer, rectal cancer, bladder cancer, lung cancer, pancreatic cancer, and thyroid cancer. Meta-analyses have also been performed to assess ATM rs1801516 polymorphism and cancer predisposition, but the results are inconsistent [ 10 14 ].…”
Section: Introductionmentioning
confidence: 99%